Gestión de la información para la difusión de las primicias de la ciudad de Riobamba - Santellán Naulasaca, Washington David (2018)
The present investigation covers very important points information management of the first fruits from Riobamba, which was submitted to ab authenticity process certification, and the development for is diffusion beginning with an information analysis, as first point we have: The analysis of the information, where it was found that the information remains in Municipal Library of Riobamba city, and then extract it from the book by Tomas Oleas Carrasco entitled “Riobamba and his fruits” published in 2000. Mr. Eduardo Chief warrior of the Municipal library of Riobamba granted a certificate of authenticity of the processed information, so that with this investigation he gave it an important and knowledge of the city about its first fruits. In recent years, technology has advance in gigantic steps, which is why the use of ICT has been considered relevant in our research project since it opens up number of possibilities to solve a problem. It fact, it has determined that, to transmit the processed information. “Android Studio” was used, which is a virtual platform to develop mobile applications. Then, tourists have available information of the scoops of the city of Riobamba in a App that is available in the web.